Antimicrobial Activity of Hexane Extracts of D. hamiltoniion Microbial Isolates of Spoiled Vegetables andPathogenic Microorganisms - VIMALA, Y.; CHANDANA KUMARI, ARUNA; ELIZABETH, K.M. (Asian Journal of Chemistry, 2010)
The antimicrobial activity of Decalepis hamiltonii was tested by disc diffusion method against microbial isolates from spoiled vegetables and pathogenic microorganisms. The crude aqueous extract, cold hexane extract hexane distillate and residual extracts of the roots were used for the study. The crude extracts showed largest zones to E. coli, i.e., 15 mm zones. The cold hexane extract showed maximum activity against P2 (isolate), B (isolate), Serratia marcescens and Rhizopus species, i.e., 15 mm. The distillate showed 6 mm zones to all the microorganisms tested. The residual extract showed maximum activity against E. coli (28 mm), Aspergillus flavus (24 mm), P1 (isolate) (20.0 mm), Candida albicans (20.0 mm) indicating that ilie residual extracts were strongly inhibitory. The results indicate that the residual extracts can be used as broad spectrum antimicrobial agents.